Circulating and urinary microRNA profile in focal segmental glomerulosclerosis: a pilot study. (28th March 2015) - Ramezani, Ali; Devaney, Joseph M.; Cohen, Scott; Wing, Maria R.; Scott, Richard; Knoblach, Susan; Singhal, Rishi; Howard, Lilian; Kopp, Jeffrey B.; Raj, Dominic S.
Abstract: Background: MicroRNAs (miRNAs) are noncoding RNA molecules that play important roles in the pathogenesis of various kidney diseases. We investigated whether patients with minimal change disease (MCD) and focal segmental glomerulosclerosis (FSGS) have distinct circulating and urinary miRNA expression profiles that could lead to potential development of noninvasive biomarkers of the disease. Materials and methods: Exosome miRNAs were extracted from plasma and urine samples of patients with primary FSGS ( n  = 16) or MCD ( n  = 5) and healthy controls ( n  = 5). Differences in miRNA abundance were examined using Affymetrix GeneChip miRNA 3.0 arrays. QRT‐PCR was used to validate the findings from the array. Results: Comparison analysis of FSGS versus MCD revealed 126 and 155 differentially expressed miRNAs in plasma and in urine, respectively. Only 38 of these miRNAs were previously cited, whereas the remaining miRNAs have not been described. Comparison analysis showed that a significant number of miRNAs were downregulated in both plasma and urine samples of patients with FSGS compared to those with MCD. Plasma levels of miR‐30b, miR‐30c, miR‐34b, miR‐34c and miR‐342 and urine levels of mir‐1225‐5p were upregulated in patients with MCD compared to patients with FSGS and controls ( P  < 0·001). Urinary levels of mir‐1915 and miR‐663 were downregulated in patients with FSGS compared to MCD and controls ( P  < 0·001), whereas the urinary levels of miR‐155 were upregulated in patients with FSGS when compared to patients with MCD and controls ( P  < 0·005). Conclusions: Patients with FSGS and MCD have a unique circulating and urinary miRNA profile. The diagnostic and prognostic potential of miRNAs in FSGS and MCD warrants further studies.